6/9=n/3

Simple and best practice solution for 6/9=n/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6/9=n/3 equation:


n in (-oo:+oo)

6/9 = n/3 // - n/3

6/9-(n/3) = 0

2/3-1/3*n = 0 // - 2/3

-1/3*n = -2/3 // : -1/3

n = -2/3/(-1/3)

n = 2

n = 2

See similar equations:

| 2x-6=9x+9 | | 2X-5y-3xy=0 | | 16x^2+70x-9=(Ax+B)(Cx-D) | | |4x-1/3|=1 | | 2x^2-16=20 | | 2X-0.5y-0.001xy=0 | | 502.4=3.14*4x^2*h | | 49w^2-25f^2= | | 2x+6=4x+20 | | .06x=1 | | (-1)-3-(-11)+(-9)= | | 5x-3(x-6)=3+3x | | -2xt^2-11=5 | | X^2+2x+2.5=0 | | 3+2x+11=6x+33 | | x-(.15x)=130 | | factorz^2+z-12= | | 21x^2y+3xy-35x-5=0 | | (X^4y^3)(xy^6)= | | n-9=3(n-15) | | 11-(3x+-5)=5x | | (3s+19)(s+1)=-20 | | x^4-x^2y^2+y^4=z^2 | | =-8(10-6r)+6r | | W+2=17 | | =-8(n-2)-7n | | 2=2+8x+2x | | =-9(1+m)-2m | | 9-3(0)/-5 | | =9(8k+2) | | 19x-5=14x-30 | | 3(4x+6)+2(6x+4)+3=24x+30 |

Equations solver categories